Immune System, Microbiota, and Microbial Metabolites: The Unresolved Triad in Colorectal Cancer Microenvironment - Hanus, Michelle; Parada-Venegas, Daniela; Landskron, Glauben; Wielandt, Ana Maria; Hurtado, Claudia; Alvarez, Karin; Hermoso, Marcela A.; López-Köstner, Francisco; De la Fuente, Marjorie (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) is one of the most common cancers worldwide. As with other cancers, CRC is a multifactorial disease due to the combined effect of genetic and environmental factors. Most cases are sporadic, but a small proportion is hereditary, estimated at around 5-10%. In both, the tumor interacts with heterogeneous cell populations, such as endothelial, stromal, and immune cells, secreting different signals (cytokines, chemokines or growth factors) to generate a favorable tumor microenvironment for cancer cell invasion and metastasis. There is ample evidence that inflammatory processes have a role in carcinogenesis and tumor progression in CCR. Different profiles of cell activation of the tumor microenvironment can promote pro or anti-tumor pathways; hence they are studied as a key target for the control of cancer progression. Additionally, the intestinal mucosa is in close contact with a microorganism community, including bacteria, bacteriophages, viruses, archaea, and fungi composing the gut microbiota. Aberrant composition of this microbiota, together with alteration in the diet‐derived microbial metabolites content (such as butyrate and polyamines) and environmental compounds has been related to CRC. Some bacteria, such as pks+ Escherichia coli or Fusobacterium nucleatum, are involved in colorectal carcinogenesis through different pathomechanisms including the induction of genetic mutations in epithelial cells and modulation of tumor microenvironment. Epithelial and immune cells from intestinal mucosa have Pattern-recognition receptors and G-protein coupled receptors (receptor of butyrate), suggesting that their activation can be regulated by intestinal microbiota and metabolites. In this review, we discuss how dynamics in the gut microbiota, their metabolites, and tumor microenvironment interplays in sporadic and hereditary CRC, modulating tumor progression.